Babesiosis: A Retrospective Review of 38 Cases in the Upper Midwest. (27th June 2019) - Fida, Madiha; Challener, Douglas; Hamdi, Ahmed; O'horo, John; Abu Saleh, Omar
Abstract: Babesiosis is an emerging health risk, and clinicians need to be aware of its different clinical manifestations. In our cohort of 38 patients, almost half did not recall a tick bite, and diagnosis was delayed due to the nonspecific nature of symptoms. Sixty-eight percent of patients required hospitalization, with 21% requiring intensive care unit stay. Coinfection with Lyme, anaplasma, or both Lyme and anaplasma was seen in 24%, 5%, and 8% of the patients, respectively. None of the patients in our cohort died from their disease.